Dark Spot in Fibrinous Central Serous Chorioretinopathy Masquerading Choroiditis. (June 2013) - Parchand, Swapnil; Gupta, Vishali; Gupta, Amod; Dogra, M. R.; Singh, Ramandeep; Sharma, Aman
Abstract Purpose: The authors observed that eyes with acute fibrinous central serous chorioretinopathy (CSC) masquerading active choroiditis had a "dark spot" within the yellow fibrinous deposit. The present study aims to describe this sign as a clinical indicator of acute serofibrinous exudative detachment, thus helping to differentiate it from active choroiditis. Method: The authors retrospectively reviewed the records of 19 patients of fibrinous CSC masquerading active choroiditis. Color fundus photographs, fundus fluorescein angiogram (FFA), and optical coherence tomography (OCT) at baseline and follow-up were studied for a dark spot. The systemic steroids were stopped and all patients were followed up. Results: There were 12 men and 7 women with a mean age of 39.8 years. Fourteen patients had received systemic steroids. Funduscopy revealed creamy yellow subretinal lesion/s simulating active choroiditis lesion in all eyes and exudative retinal detachment in 9 eyes. The dark spot was seen as a round, grayish dark spot within the fibrinous lesion in all eyes. On FFA and OCT, this dot corresponded to the site of leakage. All eyes showed resolution of CSC on follow-up. Conclusion: Detection of a dark spot within fibrinous CSC is an important clinical sign that, if present, helps to avoid misdiagnosis, unnecessary diagnostic tests, and incorrect treatment.